2020
DOI: 10.3389/fgene.2020.00317
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of an Invasive Plant, Sorghum halepense L. (‘Johnsongrass’)

Abstract: From noble beginnings as a prospective forage, polyploid Sorghum halepense ('Johnsongrass') is both an invasive species and one of the world's worst agricultural weeds. Formed by S. bicolor x S. propinquum hybridization, we show S. halepense to have S. bicolor-enriched allele composition and striking mutations in 5,957 genes that differentiate it from representatives of its progenitor species and an outgroup. The spread of S. halepense may have been facilitated by introgression from closelyrelated cultivated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 50 publications
3
28
1
Order By: Relevance
“…This kelp presents the rare characteristic of being independently cultivated in its native range and introduced in four continents outside its native range. This situation contrasts with other well-studied cases such as Oryza 33 and Sorghum 34 in which domestication preceded escape to the wild. Recent studies have demonstrated the importance of genome-wide analyses, based on whole-genome sequencing data, to understand human-driven evolutionary change, notably with respect to domestication 4 7 , with fewer studies examining invasive species 8 , 9 , and none addressing both aspects at the same time.…”
Section: Maincontrasting
confidence: 82%
“…This kelp presents the rare characteristic of being independently cultivated in its native range and introduced in four continents outside its native range. This situation contrasts with other well-studied cases such as Oryza 33 and Sorghum 34 in which domestication preceded escape to the wild. Recent studies have demonstrated the importance of genome-wide analyses, based on whole-genome sequencing data, to understand human-driven evolutionary change, notably with respect to domestication 4 7 , with fewer studies examining invasive species 8 , 9 , and none addressing both aspects at the same time.…”
Section: Maincontrasting
confidence: 82%
“…With climate change, S. halepense is predicted to spread further northward in North America, causing greater yield loss in Zea mays (corn) crops (McDonald et al, 2009). S. halepense exhibits many other evolutionary adaptations in addition to what we have listed here, enabling continual change of S. halepense populations at the northern edge of its range (Paterson et al, 2020).…”
Section: Recent Examples Of Increased Invasion Under Climate Changementioning
confidence: 84%
“…Indeed, the evolutionary novelty allowing S. halepense to colonize more northerly environments in North America has been attributed to this genetic diversity. Its rhizomes have evolved cold tolerance, even though when it was introduced in the early 1800s it was a C 4 grass adapted only to the warmer climates consistent with its origin in western Asia (McWhorter, 1971;Paterson et al, 2020). Furthermore, northern populations may exhibit an annual life history, allowing S. halepense to overwinter more readily along the northern edge of its range (Warwick et al, 1986).…”
Section: Evidence Of Rapid Evolution On Invasion Edgesmentioning
confidence: 99%
See 2 more Smart Citations